Features of heart rate variability in young people, associated with body weight - V. V. Gorban; K. S. Chernoglazov (Кубанский научный медицинский вестник, 2015)
The aim of the research was to study the characteristics of heart rate variability (HRV) criteria to detect early vegetative imbalance in young people with overweight and obesity. From 163 students with an average age of 22,2 years were conducted to study the quality of life, аnthropometry, bioimpedance test, HRV at 10-minute intervals. In the normal range of integral indicator HRV - tension index (TI) - with rising TI grew sympathetic activation and decreased the overall HRV and parasympathetic activity. Young people with increased visceral fat recorded higher values in systolic and diastolic blood pressure and TI. The level of visceral fat has determinating effect on the sympatho-vagal balance, modulation which reliably reflects indicator HRV - TI.